The days of our lives: deep acting, surface acting and actors' health : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Green, Mike (Massey University, 2009)
Although emotional labour has been studied extensively among work populations such as doctors, detectives and adventure tourism guides, there has been no known research on the psychology of actors and acting within an emotional labour framework. This investigation had two purposes. The first was to extend what is currently known about two emotional labour strategies: surface acting, the regulation of observable expressions of emotions, and deep acting, the regulation of felt emotions, to include actual actors. The dependent variables used in this study were job and life satisfaction. The second purpose was to examine whether having a sense of community moderated the relationship between surface acting, deep acting and the dependent variables. Responses from 89 professional, amateur and community theatre actors were analysed. Pearson’s correlation coefficients showed a significant relationship between surface acting and the dependent variables. Hierarchical regression results showed a significant moderation effect for sense of community on the relationship between deep acting and life satisfaction. Implications, limitations, and directions for future research are discussed.
Keywords: Emotional labour; Sense of community; Life satisfaction; Job satisfaction; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380199 Psychology not elsewhere classified